2017
DOI: 10.1016/j.jksues.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical behavior of stir-cast Zn–27Al based composites reinforced with rice husk ash, silicon carbide, and graphite

Abstract: The microstructure and mechanical properties of Zn-27Al based composites reinforced with rice husk ash (RHA), silicon carbide (SiC), and graphite (C g ) particles have been investigated. The Zn-27Al composites consisting of varied weight ratios of the reinforcing materials were produced using the stir casting process. Hardness test, tensile properties evaluation, fracture toughness determination, and microstructural examination, were used to characterize the composites produced. Results show that the microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The production of the Zn-27Al alloy matrix composites with steel machining chips and graphite as reinforcements was performed using double stir casting in agreement with [15]. The amount of reinforcements (steel machining chips and graphite) required to prepare five composite compositions presented in Tab.…”
Section: Composites Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of the Zn-27Al alloy matrix composites with steel machining chips and graphite as reinforcements was performed using double stir casting in agreement with [15]. The amount of reinforcements (steel machining chips and graphite) required to prepare five composite compositions presented in Tab.…”
Section: Composites Productionmentioning
confidence: 99%
“…The testing procedure and data analysis were done in accordance with ASTM E8M-15a [17] standard. Fracture toughness of the Zn-27Al composites was determined using circumferential notch tensile (CNT) testing approach in accordance with [15]. using a Universal tensile testing machine.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…The material used in a excellent machining study were used. 4 In this aluminum Sic composite were prepared in a different weight percentage. And the different loading wear tested were carry out.…”
Section: Introductionmentioning
confidence: 99%
“…AlBeMet material has a low CTE, high specific heat and high thermal conductivity these properties are favorable for various space and aerospace applications. Many researchers [24][25][26][27][28][29][30][31] revealed that the liquid metallurgy route (stir casting) is one of the utmost extensively used and economical processing techniques for the fabrication particulate MMCs. In the present investigation, aluminum 7075 alloys as matrix and Al7075/Beryl-Graphene MMCs were developed by using stir casting with varying percentage of Graphene from 0.5wt% to 2wt% in steps of 0.5 and fixed percentage (6wt.…”
Section: Introductionmentioning
confidence: 99%